Military Technology In 2100: The Evolution Of Defense Toward A Futuristic Era - Snekubun, Elyakim; Wiranto, Surya; Hilmansyah, Ceppi (Cita konsultindo, 2025)
This article explores anticipated shifts in military technology through the year 2100 by synthesizing present-day technological trajectories, scientific advancements, and evolving defense policies. Over the coming century, defense architectures are likely to transform substantially, marked by pervasive combat automation, sophisticated exoskeleton systems, adaptive smart-material camouflage, and the incorporation of genetic and biotechnological applications for defense purposes. Control of cyberspace and outer space will emerge as pivotal strategic arenas. Together, these trends will reframe warfare from primarily kinetic encounters to conflicts driven by advanced technologies and data-centric operations. Developments in artificial intelligence, machine learning, and autonomous weapons are expected to lessen direct human involvement while accelerating and streamlining military decision-making processes (Scharre, 2018). However, these innovations raise serious concerns automated escalation, erosion of meaningful human oversight, and potential unethical deployment of powerful technologies highlighting the pressing need for robust international legal and ethical governance. This paper offers a detailed examination of these trajectories and their implications for global military capabilities and international security in the twenty-second century.